CHARACTERISTICS OF ENVIRONMENTAL GEOCHEMISTRY IN SURFACE SEDIMENT OF TAM GIANG - CAU HAI LAGOON FORMATIONS (THUA THIEN HUE PROVINCE) - Khoi, Nguyen minh; Anh, Vu Thu; Hiep, Pham Quoc; Quang, Ngo Van; Pho, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2007)
In this paper introduced the results of a new study on the characteristics of environmental geochemistry in surface sediment of Tam Giang - Cau Hai lagoon formations. That is environmental factors that designed the sediment formations such as Ph, Eh, and contribution of the elements in sediment such as N, P, C, S, and heavy metals. By comparison with the previously results that are  associated with observation of seasons were taken the variational trend of sedimentary environment in study area